If \( a_1, a_2, a_3, \ldots a_n \) are in an Arithmetic Progression with common difference \( d \neq 0 \), then prove that
sin(d)×(csc(a1)×csc(a2)+csc(a2)×csc(a3)+…+csc(an−1)×csc(an))=cot(a1)−cot(an.) \sin (d) \times ( \csc (a_1) \times \csc (a_2) + \csc (a_2) \times \csc (a_3) + \ldots + \csc (a_{n-1}) \times \csc (a_n) ) = \cot( a_ 1 )- \cot (a_n.) sin(d)×(csc(a1)×csc(a2)+csc(a2)×csc(a3)+…+csc(an−1)×csc(an))=cot(a1)−cot(an.)
Note by Calvin Lin 6 years, 11 months ago
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
_italics_
**bold**
__bold__
- bulleted- list
1. numbered2. list
paragraph 1paragraph 2
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
This is a quote
# I indented these lines # 4 spaces, and now they show # up as a code block. print "hello world"
\(
\)
\[
\]
2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
@Kandarp Singh I believe that you will get better response posting this as a note for discussion, instead of as a question looking for a numerical answer.
Log in to reply
ok
First open all the terms to get LHS=sin(d)csc(a1)csc(a2)+sin(d)csc(a2)csc(a3)+................sin(d)csc(an−1)csc(an)=sin(d)sin(a1)sin(a2)+sin(d)sin(a2)sin(a3)+............+sin(d)sin(an−1)sin(an).LHS=sin(d)csc({ a }_{ 1 })csc({ a }_{ 2 })+sin(d)csc({ a }_{ 2 })csc({ a }_{ 3 })+................sin(d)csc({ a }_{ n-1 })csc({ a }_{ n })\\ =\frac { sin(d) }{ sin({ a }_{ 1 })sin({ a }_{ 2 }) } +\frac { sin(d) }{ sin({ a }_{ 2 })sin({ a }_{ 3 }) } +............+\frac { sin(d) }{ sin({ a }_{ n-1 })sin({ a }_{ n }) } .LHS=sin(d)csc(a1)csc(a2)+sin(d)csc(a2)csc(a3)+................sin(d)csc(an−1)csc(an)=sin(a1)sin(a2)sin(d)+sin(a2)sin(a3)sin(d)+............+sin(an−1)sin(an)sin(d).
Now since a1,a2,......an{ a }_{ 1 },{ a }_{ 2 },......{ a }_{ n }a1,a2,......an are in A.P.A.P.A.P.
d=a2−a1=a3−a2=............=an−an−1.d={ a }_{ 2 }-{ a }_{ 1 }={ a }_{ 3 }-{ a }_{ 2 }=............={ a }_{ n }-{ a }_{ n-1 }.d=a2−a1=a3−a2=............=an−an−1.
Now replacing ddd suitably we get
LHS=sin(a2−a1)sin(a1)sin(a2)+sin(a3−a2)sin(a2)sin(a3)+............+sin(an−an−1)sin(an−1)sin(an).LHS=\frac { sin({ a }_{ 2 }-{ a }_{ 1 }) }{ sin({ a }_{ 1 })sin({ a }_{ 2 }) } +\frac { sin({ a }_{ 3 }-{ a }_{ 2 }) }{ sin({ a }_{ 2 })sin({ a }_{ 3 }) } +............+\frac { sin({ a }_{ n }-{ a }_{ n-1 }) }{ sin({ a }_{ n-1 })sin({ a }_{ n }) } .LHS=sin(a1)sin(a2)sin(a2−a1)+sin(a2)sin(a3)sin(a3−a2)+............+sin(an−1)sin(an)sin(an−an−1).
Using identity sin(A−B)=sin(A)cos(B)−sin(B)cos(A)sin(A-B)=sin(A)cos(B)-sin(B)cos(A)sin(A−B)=sin(A)cos(B)−sin(B)cos(A) we get
sin(A−B)sin(A)sin(B)=sin(A)cos(B)−sin(B)cos(A)sin(A)sin(B)=cot(B)−cot(A).\frac { sin(A-B) }{ sin(A)sin(B) } =\frac { sin(A)cos(B)-sin(B)cos(A) }{ sin(A)sin(B) } =cot(B)-cot(A).sin(A)sin(B)sin(A−B)=sin(A)sin(B)sin(A)cos(B)−sin(B)cos(A)=cot(B)−cot(A).
Now our LHSLHSLHS becomes =(cot(a2)−cot(a1))+(cot(a3)−cot(a2))+...........+(cot(an)−cot(an−1))=\quad (cot({ a }_{ 2 })-cot({ a }_{ 1 }))+(cot({ a }_{ 3 })-cot({ a }_{ 2 }))+...........+(cot({ a }_{ n })-cot({ a }_{ n-1 }))=(cot(a2)−cot(a1))+(cot(a3)−cot(a2))+...........+(cot(an)−cot(an−1))
Note how terms cancel here hence LHSLHSLHS becomes =cot(an)−cot(a1)=RHS=\quad cot({ a }_{ n })-cot({ a }_{ 1 })=RHS\quad =cot(an)−cot(a1)=RHS
HenceprovedHence\quad provedHenceproved
The RHSRHSRHS kinda suggests that this is telescopical. Indeed, sin(d)∗csc(an)∗csc(an+1)=sin(an+1−an)sin(an)∗sin(an+1)sin(d)*csc(a_n)*csc(a_{n+1})=\frac {sin(a_{n+1}-a_{n})}{sin(a_n)*sin(a_{n+1})}sin(d)∗csc(an)∗csc(an+1)=sin(an)∗sin(an+1)sin(an+1−an) Using the difference formula, it simplifies to cot(an)−cot(an+1)cot(a_n)-cot(a_{n+1})cot(an)−cot(an+1).
Hence LHS=cot(a1)−cot(a2)+cot(a2)−cot(a3)+...+cot(an−1)−cotan=cot(a1)−cot(an)cot(a_1)-cot(a_2)+cot(a_2)-cot(a_3)+...+cot(a_{n-1})-cot{a_n}=cot(a_1)-cot(a_n)cot(a1)−cot(a2)+cot(a2)−cot(a3)+...+cot(an−1)−cotan=cot(a1)−cot(an)
Problem Loading...
Note Loading...
Set Loading...
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
@Kandarp Singh I believe that you will get better response posting this as a note for discussion, instead of as a question looking for a numerical answer.
Log in to reply
ok
First open all the terms to get LHS=sin(d)csc(a1)csc(a2)+sin(d)csc(a2)csc(a3)+................sin(d)csc(an−1)csc(an)=sin(a1)sin(a2)sin(d)+sin(a2)sin(a3)sin(d)+............+sin(an−1)sin(an)sin(d).
Now since a1,a2,......an are in A.P.
d=a2−a1=a3−a2=............=an−an−1.
Now replacing d suitably we get
LHS=sin(a1)sin(a2)sin(a2−a1)+sin(a2)sin(a3)sin(a3−a2)+............+sin(an−1)sin(an)sin(an−an−1).
Using identity sin(A−B)=sin(A)cos(B)−sin(B)cos(A) we get
sin(A)sin(B)sin(A−B)=sin(A)sin(B)sin(A)cos(B)−sin(B)cos(A)=cot(B)−cot(A).
Now our LHS becomes =(cot(a2)−cot(a1))+(cot(a3)−cot(a2))+...........+(cot(an)−cot(an−1))
Note how terms cancel here hence LHS becomes =cot(an)−cot(a1)=RHS
Henceproved
The RHS kinda suggests that this is telescopical. Indeed, sin(d)∗csc(an)∗csc(an+1)=sin(an)∗sin(an+1)sin(an+1−an) Using the difference formula, it simplifies to cot(an)−cot(an+1).
Hence LHS=cot(a1)−cot(a2)+cot(a2)−cot(a3)+...+cot(an−1)−cotan=cot(a1)−cot(an)